Nurturing a research culture in the counseling practice - Salazar-Clemeña, Rose Marie (Philippine Journal of Counseling Psychology, 2009)
The author describes the dynamics surrounding research productivity among counselors in the Philippine setting by presenting results of a pilot survey on counselors' interest and experience in research. On the basis of the findings, she offers recommendations for nurturing a research culture to three major entities: counselor education programs, institutions employing counselors, and professional organizations. She concludes with recommendations for counseling practitioners themselves.